(untitled) (Journal of Preventive and Social Medicine, 2021)
Background: To determine ability of cervical cerclage to improve pregnancy outcome in patients having cervical incompetence. Methods: A retrospective study was conducted at Central Hospital Limited, Dhanmondi, Dhaka on 35 patients. All had history of one or more mid trimester abortion and were subjected to cervical cerclage (McDonald suture). Results: Average pregnancy prolongation was 17 weeks. Just over half of these women (51%) delivered at term and just over half the newborns (51%) weighed above 2.5 kg. Over 11% had abortion, 14% had preterm PROM and 14% preterm labour. Term PROM was the outcome in 5.7% and cervical injury occurred in 8.6%. Conclusion: Cervical cerclage is beneficial for pregnancy with cervical insufficiency and hence placement of cervical cerclage can reduce early pregnancy loss. JOPSOM 2020; 39(2): 70-73